Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.jfluidstructs.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

On the fluid-structure interaction of flexible membrane wings for MAVs in and out of ground-effect

Abstract: Wind tunnel experiments are conducted at a Reynolds number of Re = 56,000, measuring rigid flat-plates and flexible membrane wings from free-flight into ground-effect conditions. Load cell measurements, digital image correlation and particle image velocimetry are applied in high-speed to resolve time-synchronised lift, drag and pitch oscillations simultaneously with membrane and flow dynamics. Proper orthogonal decomposition is applied on flow oscillations to determine their spatiotemporal evolution. Loads, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
34
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 37 publications
9
34
0
2
Order By: Relevance
“…This physical interpretation takes inspiration in Connell and Yue (2007) with the description of the snapping event of a flag, where similarly there is a peak of tension during the strong acceleration which is associated with a shedding of strong vortices. For 2D membranes, Rojratsirikul et al (2011) also present reduced frequencies similar to the ones found in the present work (see Table 1), confirmed by Bleischwitz et al (2017). They suggest that the membrane vibrations might be coupled with the first harmonic of the natural vortex shedding frequency at high incidence.…”
Section: Proposition Of a Physical Mechanism Of The Flapping Phenomenonsupporting
confidence: 89%
“…This physical interpretation takes inspiration in Connell and Yue (2007) with the description of the snapping event of a flag, where similarly there is a peak of tension during the strong acceleration which is associated with a shedding of strong vortices. For 2D membranes, Rojratsirikul et al (2011) also present reduced frequencies similar to the ones found in the present work (see Table 1), confirmed by Bleischwitz et al (2017). They suggest that the membrane vibrations might be coupled with the first harmonic of the natural vortex shedding frequency at high incidence.…”
Section: Proposition Of a Physical Mechanism Of The Flapping Phenomenonsupporting
confidence: 89%
“…Research in this field has shown that membrane wings can have a steeper lift slope as well as higher/smoother stall angles and an overall higher performance due to the fluid structure interaction (Arbos Torrent 2013;Rojratsirikul 2010;Fairuz et al 2016;Gordnier, and Attar, 2014;. The unsteady effects of the membrane vibrations can also affect separated regions of flow, significantly changing the foil's performance (Rojratsirikul, 2010;Bleischwitz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Bleischwitz et al. 17 studied the fluid–solid coupling phenomenon of flexible plates under-ground effect by experiments and concluded that the locomotion performances of flexible plates under ground effect are better than those of rigid plates. Quinn et al.…”
Section: Introductionmentioning
confidence: 99%
“…So far there have been many studies on the ground effect of airfoil and fluid–solid interaction of flexible thin plates and airfoils. 218 Previous studies have shown that the presence of ground effects can lead to an increase in lift, and flexible airfoils and thin plates generally have better locomotion performance over rigidity. However, no work has systematically studied the effect of flexibility changes on the characteristics of the force and deformation of the flexible wing.…”
Section: Introductionmentioning
confidence: 99%